Too big to fail after FDICIA - Larry D. Wall (Economic Review, 2010)
In 1993, when this article was originally published, Congress had recently passed the Federal Deposit Insurance Corporation Improvement Act of 1991 (FDICIA) to reduce taxpayers' exposure to financial system losses, including their exposure at too big to fail financial institutions. In his new preface, the author observes that, by passing FDICIA, Congress was signaling that it was serious about ending 100 percent de facto deposit insurance. He notes that FDICIA's least-cost resolution provisions were partially successful, terminating 100 percent de facto deposit insurance for most banks. The recent financial crisis demonstrated, though, that too big to fail has still not been eliminated for the very largest banks. To provide a background for the debate about what should be done to eliminate the persistent problems with existing too big to fail policies, this article outlines what Congress originally intended FDICIA to accomplish. From its 1993 perspective, the article reviews the controls FDICIA placed on regulators' ability to protect or extend the lives of large banks while keeping other policy tools for dealing with systemic risk. The article also discusses some lingering systemic risk issues, including the effect of a large bank's failure on financial derivatives markets and the effect of unexpected massive losses at one or more banks, as well as FDICIA's provisions designed to reduce systemic risk.
Keywords: G21; G28; 330; too big to fail; FDICIA